Paraganglioma of the vagina: a case report and review of the literature - Cai, Tao (Dove Medical Press, 2014)
Vaginal paraganglioma is a rare and unusual tumor occurring in the vaginal wall. It is a solitary primary paraganglioma, especially in atypical sites. Herein, we report an unusual case of a 17-year-old woman who had not experienced vomiting, or hypertension. She was found to have an immobile solid mass in the right side of her vaginal wall. Positron emission tomography/computed tomography scans revealed a well-defined solid ovoid mass adjacent to the bladder and pelvic floor. Tumor markers were within the normal range. A transient blood pressure increase occurred during the biopsy. After oral administration of antihypertensive drugs, surgery was performed to completely remove the mass. Histopathological examination indicated that it was a paraganglioma of the vagina. Repeat computed tomography examination did not reveal any local recurrence or distant metastasis during the 12-month follow-up period.